Modified culture assay to obtain a diversity of hyphal structures of Ceratobasidium theobromae-VSD pathogen on cocoa - Muhammad Junaid; DAVID GUEST (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Junaid M, Guest D. 2021. Modified culture assay to obtain a diversity of hyphal structures of Ceratobasidium theobromae, VSD pathogen on cocoa. Biodiversitas 22: 1879-1886. Ceratobasidium theobromae, a causal agent of vascular streak dieback (VSD) disease, is a fastidious Basidiomycete fungus devastating cocoa in Southeast Asia Melanesia. One sought-after in vitro technique is pathogen subculture. As an obligate parasite, growing the pathogen onto an artificial medium is always problematic. In this paper, a new design is demonstrated to obtain a single colony of the pathogen with hyphal diversity. Putative C. theobromae is obtained from infected leaves and petioles of cocoa using rigorous surface sterilization before culturing on standard water agar (WA) medium. Once the fungus grows out from the tissue, the infected plant tissue is then removed carefully, leaving mycelium's uninterrupted growth. About 200 mL of liquid Corticium culture medium (CCM) is injected to submerge the solid medium layer, nurture hyphae development, and allow generative structure formation. Molecular amplification with a pair primer of ITS 1B (forward) and 4B (reverse) specific for fungal Basidiomycete DNA with a touchdown undertook thermal cycler program. PCR product amplification successfully confirmed the presence of C. theobromae DNA collected from the samples with VSD symptomatic lesions and identified a diversity of hyphal and branching formations.